Writing and mask : Semiotic and poetic approach - (:unkn) unknown (My University, 2017)
Questions about the existence of writing in Africa have always interested intellectual circles, between those who think that writing on the continent is a new phenomenon resulting from colonization, and those who challenge it. The present thesis proposes to analyze the presence of the writing in the traditional Fang society, and to demonstrate that every society has that will of inscription of meaning in order to perpetuate the collective memory (rites, beliefs and social organization). It is through the mask that that problematic will be studied: the mask as the means of reading that "thought of writing". The second stage of this work, will deal with the mask in literature, through its different levels of apprehension (cultural mask and social mask) without considering them as heterogeneous, but to emphasize its complementarity. Then, this work will also highlight how the literary writing appropriates the functioning of the mask in two authors: Ludovic Obiang and Sami Tchak, through concealment or veil. The interest here is to reconsider the position of traditional symbols in contemporary African literature, as an attempt to answer to current questions.
Keywords: African Research